The Development of a Calibration Methodology for a Realistic Primary Settling Tank (PST) Model - Matesun, Joshua (Faculty of Engineering and the Built Environment, 2023)
The comprehensive characterisation of influent waste to water and resource recovery facilities (WRRFs) is key to tracking the material elements through the entire WRRF system to ensure accurate prediction of system behaviour/performance or avoidance of system failure. Current models for activated sludge (AS) and anaerobic digestion (AD) unit processes of WRRF are well verified. However, previous models that replicated primary sedimentation units assumed that all the total settleable solids (TSS) components settled at the same velocities, which resulted in poor predictions of primary sludge characteristics and subsequently poor AD model predictions (with the PST underflow linked to AD in plant-wide settings). In this investigation, the raw wastewater entering the WRRF via the primary settling tank (PST) is comprehensively characterised by categorising the TSS according to inorganic settleable solids (ISS), biodegradable particulate organics (BPO) and unbiodegradable particulate organics (UPO), each with five settling velocity distributions profiles. The BPO is further defined in terms of its elemental composition and hydrolysis rate kinetic constants to allow for accurate prediction of the AD system performance, when linked to the virtual PST. With the composition of raw wastewater and primary sludge (PS) known the settled wastewater that leads to the activated sludge (AS) system can be determined using the principles of material mass balance over the PST unit process. This project introduces (i) the modification of the University of Cape Town Primary Sedimentation Unit (UCTPSU) physical process model of Polorigni (2020), by the inclusion of hydrolysis and acid fermentation bio-processes and (ii) calibration of the UCTPSU model through (a) the performance of a sensitivity analysis on the modified UCTPSU model and (b) utilisation of information generated from settleometer tests and augmented bio-methane potential (ABMP) tests to accurately predict the characteristics of PS to AD and settled wastewater to AS systems, hence allow for accurate tracking of elements along the entire WRRF, when using the model for design and optimised operation of WRRF systems. The settleometer, AD and ABMP tests showed that primary sewage sludge (or the total settleable solids) fractionated according to the particle size and density, and their corresponding wastewater characteristics were determined. The findings also showed that the unbiodegradable particulate organics formed the largest total settleable solid components removed from the PST underflow.